K-pop, Neoliberalismo y Crisis de Salud Mental: Una aproximación desde la canción Shadow de BTS - Cueva Naveas, Ariana (2024)
This analysis explores the interconnection between the global mental health crisis and the expansion of neoliberalism through the song “Interlude: Shadow” by BTS. It addresses the relevance of K-pop music as a vehicle for examining the effects of postmodernity and neoliberalism on people’s lives. Through an initial theoretical review, relevant concepts such as consumption-oriented perceptions of success and pressure for personal performance are discussed. The second part of the analysis focuses on the music video for “Shadow,” highlighting the internal struggles of BTS members and their critique of the demands for success and well-being in a neoliberal context. This study reveals how music serves as a platform to raise awareness of mental health issues in an era dominated by self-exploitation and the pursuit of performance.